Killing - Tsukamoto, Shinya; Hayashi, Satoshi; Ikematsu, Sôsuke; Aoi, Yû; Nakamura, Tatsuya (Third Window Films, 2020)
In exchange for board and lodging, lightning-fast samurai Mokunoshi is helping out in the everyday lives of a couple of local farmers. To keep in shape, he trains with bright farmer's son Ichisuke, while sister Yu furtively watches them. When the ronin Sawamura (played by director Tsukamoto) suddenly appears, asking Mokunoshi to go on a mission in Edo, and at the same time a bunch of bandits are lurking on the edge of the village, the peaceful existence of the three comes under threat. [Cover]
Keywords: Blu-Ray-Disc